Mozambique : First Review Under the Policy Support Instrument and Request for Modification of Assessment Criteria-Staff Report; and Press Release. (IMF Staff Country Reports; Country Report ;, 2010)
Mozambique continues to show a strong economic performance. The inflation expectations require a tightening of the macroeconomic policy mix. Executive Directors commended the role of government in sustaining economic growth by accelerating the public investment program. Engaging development partners and civil society to make the growth strategy more inclusive and allowing Mozambicans to participate in economic growth and the determination in fighting inflation is welcome. The fuel price policy has contributed to substantial costs to Mozambique's fiscal and external accounts, and poses future risks.